The Role of Financial Technology in The Revitalization of Islamic Banking Financial Inclusion in Indonesia - Muhammad Akbar Taufiqulhakim; Muhammad Reza Atallah (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten, 2021)
There are still many Islamic bank service products that are not widely accessed by customers and the increasing number of technology-based developing businesses, so Islamic banks must collaborate with financial technology to increase their role to be more inclusive. This paper aims to find out about the role of Financial Technology in increasing financial inclusion in Islamic banks and from the aspects of benefit, opportunity, cost and risk (BOCR) because Fintech in Indonesia is a big opportunity that has not been exploited more massively and systematically in taking these opportunities. The methodology used in this research is normative legal research refreshing law and book literature. Based on the results of the research, the authors conclude that fintech plays a very important role in increasing financial inclusion in Islamic banking with great opportunities that can develop progressively that will make it easier and closer to customers, Islamic banking can access financial service products offered and apply for direct financing. The fast-paced FinTech industry opens up positive opportunities for Islamic banking to undertake strategic partnerships with the FinTech industry as an integral, customer-oriented part. keywords: Financial Technology, Financial Inclusion, Sharia Banking.